2014
DOI: 10.1162/jocn_a_00537
|View full text |Cite
|
Sign up to set email alerts
|

White Noise Improves Learning by Modulating Activity in Dopaminergic Midbrain Regions and Right Superior Temporal Sulcus

Abstract: In neural systems, information processing can be facilitated by adding an optimal level of white noise. Although this phenomenon, the so-called stochastic resonance, has traditionally been linked with perception, recent evidence indicates that white noise may also exert positive effects on cognitive functions, such as learning and memory. The underlying neural mechanisms, however, remain unclear. Here, on the basis of recent theories, we tested the hypothesis that auditory white noise, when presented during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 50 publications
3
47
0
1
Order By: Relevance
“…The following hypotheses were proposed. Firstly, consistent with reports that the beneficial effects of white noise may be mediated by dopaminergic circuitry 10 , together with the beneficial effect of dopamine on word learning 20 , it was predicted that word learning would be improved in white noise relative to silence. Secondly, it was predicted that any improvements to word learning in the presence of white noise would be related to attention, being larger in persons with lower executive control of attention.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The following hypotheses were proposed. Firstly, consistent with reports that the beneficial effects of white noise may be mediated by dopaminergic circuitry 10 , together with the beneficial effect of dopamine on word learning 20 , it was predicted that word learning would be improved in white noise relative to silence. Secondly, it was predicted that any improvements to word learning in the presence of white noise would be related to attention, being larger in persons with lower executive control of attention.…”
Section: Introductionsupporting
confidence: 69%
“…Previous research has illustrated that white noise has the capacity to improve recognition memory 10 , the speed of arithmetic calculations 3 and the speed of perceptual judgements of scene images 11 in healthy adults (but see also below re null findings). The current results extend these findings, demonstrating that white noise can also boost the lexical acquisition of novel word forms in healthy adults.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As further support for the SR view a recent study showed neurophysiological effects on EEG/ERP of noise exposure during a GoNogo task where the P300 signal increased in the children that did benefit from noise (Baijot et al, 2016). Furthermore, a recent fMRI study found increased activity in dopaminergic areas of the brain in healthy adult controls exposed to noise during cognitive task performance (Rausch et al, 2014). Future research has to use brain-imaging techniques to investigate the mechanisms of noise benefit further.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in our model we are suggesting that the boosting that occurs for the signal (Simon) allows it to be sensed and communicated onward through the thalamus (the wall) to the limbic (Lilly) and neocortical (Neo) areas by the facilitatory effects of DAS/BLS (the boxes), which create the AIP equivalent of "white noise" at the thalamic level. One research group has proposed that in both age-related states and brain disorders that feature memory deficits linked to abnormal functioning in the mesolimbic region, this "white noise" may facilitate learning through the restoration of functioning in the mesolimbic system (Rausch, Bauch, & Bunzeck, 2014).…”
Section: Sr and The Prediction Of Successful Clinical Outcomesmentioning
confidence: 99%